Transition Countries in 2003: Reforms and Restructuring Keep the Global Economic Slowdown at Bay - Peter Havlik (The Vienna Institute for International Economic Studies (wiiw), 2003)
Despite the unfavourable external economic climate over the past three years, the transition countries have displayed a reasonably good growth performance. The region as a whole has expanded more rapidly than the EU; it is also catching up in terms of productivity - especially in manufacturing. As of mid-2003, there are few signs of the protracted global economic slowdown threatening the transition countries' short- and medium-term growth prospects to any marked degree. Scheduled to join the EU in May 2004, a number of countries in Central and Eastern Europe which have attracted appreciable amounts of FDI recently improved their competitive position by securing larger export shares in the EU market. Russia continues to cash in on high revenues from energy exports; its GDP growth is accelerating while investments recover. Whereas some of the latecomers to reform and stabilization in the Balkans (Bulgaria, Romania and Croatia) have been rapidly catching up in many respects, the situation in most countries in the Western Balkans remains precarious. The economies of the transition countries in Central and Eastern Europe will grow on average by about 3% in both 2003 and 2004 - somewhat faster than over the period 2001 2002 and outstripping the eurozone again. A slow, but steady acceleration of GDP growth is forecast for Poland. Russia and Ukraine will also experience swifter growth in 2003, only to take time out in 2004. Inflation continues to drop to single-digit annual rates throughout the region (with the exception of Romania, Serbia & Montenegro and Russia), yet it is still higher than in the eurozone (except perhaps for the Czech Republic and Poland). Unemployment displays a similar pattern. Given the current gaps in labour productivity and efficiency reserves, the present modest rates of economic growth do not make for the creation of additional jobs. Although generally quite high, current account deficits in the EU accession countries are of no immediate concern as their financing is secured via capital inflows. This is not the case in the Western Balkans; Russia and Ukraine, however, continue to enjoy current account surpluses, with Russia slowly starting to attract an increasing volume of FDI as well.
Keywords: O52; O57; P24; P27; P33; P52; 330; Central and East European transition countries; forecast; East-West trade; industry; structural and technological change; exchange rates; EU enlargement